Tribologically induced nanolaminate in a cold-sprayed WC-reinforced Cu matrix composite: a key to high wear resistance. (15th November 2019) - Zhang, Yinyin; Choudhuri, Deep; Scharf, Thomas W.; Descartes, Sylvie; Chromik, Richard R.
Abstract: A self-organized 2D nanolaminate with an average lamella thickness of ~22 nm was formed in the subsurface of a cold-sprayed WC-reinforced metal matrix composite (MMC) Cu-MoS2 -WC during oscillatory sliding and it was responsible for the much more stable friction and improved wear resistance. Using high resolution transmission electron microscopy and nanoindentation, three important characteristics were observed in the nanolamellae that contributed to their great stability and high hardness. First, misorientation of the lamellar boundaries was low i.e. <3°. Second, stacking faults and twins were main substructures. Lastly, the recrystallization was controlled by grain boundary nucleation, that required much higher driving force than triple junction nucleation. Such nanolaminate eliminated massive detachment and permitted small detached particles that tended to be trapped in the contact and experienced rapid recrystallization. The equiaxed nanograins on the top surface accommodated shear force by grain boundary-mediated deformation mechanisms, which could potentially benefit tribological performance. Observations of the tribologically induced microstructural evolutions near the surface showed the formation of self-organized tribomaterial with high hardness and stability, which was aided by the presence of WC particles. Considering the effectiveness of these microstructures, future design of wear resistant alloys may consider engineering these microstructures in the as-prepared state. Graphical abstract: Unlabelled Image Highlights: A self-organized 2D nanolaminate was formed at the sliding interface of a WC-reinforced MMC. The nanolaminate featured high hardness and great stability Those features resulted from low-misorientation interface between lamellae and grain boundary-controlled recrystallization. The results demonstrate wear resistant materials can be designed through self-organization or pre-surface engineering.